Growth and gut comfort of healthy term infants exclusively fed with a partially hydrolysed protein-based infant formula: a randomized controlled double-blind trial - Kantaras, Paris; Kokkinopoulou, Anna; Hageman, Jeske H. J.; Hassapidou, Maria; Androutsos, Odysseas; Kanaki, Maria; Bovee-Oudenhoven, Ingeborg; Karaglani, Eva; Kontochristopoulou, Aikaterini-Maria; Bos, Rolf; Manios, Yannis (Frontiers in Pediatrics, 2024)
Objective: This study aimed to investigate growth and gut comfort of healthy infants fed with a partially hydrolysed cow's milk protein-based infant formula (pHF) compared to a standard intact cow's milk protein-based formula (IPF). Methods: A double-blind, multi-center, randomized, controlled trial was performed. Healthy full-term, exclusively formula-fed infants (n=345), aged ≤28 days were allocated to consume either a pHF (n=173) or an IPF (n=172) until the age of 17 weeks. The primary outcome was equivalence of weight gain (g/d) until the age of 17 weeks. The secondary outcomes were equivalence of other growth parameters, i.e., infants' weight, length, head circumference, body mass index (BMI) and anthropometric Z-scores, while tertiary outcomes were gut comfort, formula intake, and adverse events (AEs). Results: Overall, 288 infants completed the study (pHF group: 138, IPF group: 150). No differences were observed between the two groups in weight gain (g/d) during the three-months intervention (p=0.915 for the Per Protocol (PP) population). The 90% CI was [-1.252 -1.100] being within the pre-defined equivalence margin of ±3.0 g/d. Similar findings were observed in the Full Analysis Set (FAS) and the sensitivity analysis. Regarding the secondary outcomes, no differences over the intervention period were shown between the two groups in both the PP and FAS analysis sets. Average Z-scores were in the normal range based on World Health Organization (WHO) growth standards for both groups at all time points in both analysis sets. Stool consistency, amount, and colour were different in the two groups. No differences were observed in gut comfort, stool frequency, and formula intake, between the two groups. In total 14 AEs and 22 serious adverse events (SAEs) were reported of which 15 (12%) and 1 (5%) were considered as (possibly) related to the study product, respectively. Conclusions: The study demonstrates that the consumption of pHF results in adequate infant growth, equivalent to that of infants consuming IPF. Furthermore, the overall gut comfort was comparable between the two groups. Therefore, it can be concluded that the pHF is safe for and well tolerated by healthy infants.Clinical Trial Registry Number: NL9536